P36. Using opioid-induced bilateral vestibular dysfunction to validate the Head Impulse Testing Device – Functional Test (HITD-FT). Issue 8 (August 2015) - Ramaioli, C.; Colagiorgio, P.; Saglam, M.; Heuser, F.; Schneider, E.; Ramat, S.; Lehnen, N.
<x xml:space="preserve">Abstract</x> Introduction Patients with bilateral vestibular dysfunction cannot fully compensate passive head rotations with eye movements, and therefore experience oscillopsia, making everyday activities, such as walking or driving harder to undertake. Their dynamic vision during passive head movements depends on their residual vestibulo-ocular reflex (VOR) function and on re-fixation saccades. The Head Impulse Testing Device – Functional Test (HITD-FT) is a recently proposed and innovative technique for assessing dynamic vision during passive high-acceleration head rotations, mimicking natural everyday movements. Goals To validate the HITD-FT as a tool to assess the performance of the vestibulo-ocular reflex (VOR) and the effect of re-fixation saccades on the overall dynamic visual function in opioid-induced bilateral vestibular dysfunction. Materials and methods The opioid remifentanil was continuously administrated in 14 healthy men (median age 26 years, range 21–31) in order to reversibly induce a bilateral vestibular impairment. Each subject was tested with the HITD-FT before and during opioid administration. In each test, passive, unpredictable, high-acceleration (2000–7000°/s2) and small amplitude (10–20°) the ects-FT score mirrorice comched 300°/srdmic visual function matters. Unctionality, i.e. disturbing oscillopsia lity to com head rotations where applied while subjects fixated a visual stimulus. The visual stimulus consisted of a standard Landolt ring and appeared on a screen 80 ± 2 ms after head acceleration reached 300°/s2. Subjects were asked to identify the orientation of the ring and the provided answers were analyzed together with eye and head movements recorded with EyeSeeCam system. Results Before opioid application, VOR and dynamic reading performances were intact (head-impulse gain: 0.87 ± 0.08, mean ± SD; HITD-FT rate of correct answers: 90 ± 9%). The opioid administration induced impairment in the VOR function (head-impulse gain 0.63 ± 0.19) and in dynamic reading (HITD-FT 26 ± 15%) in 12/14 subjects. HITD-FT scores correlated with head-impulse gain impairment (R = 0.63, p = 0.03) and with gain difference (before/during opioid R = −0.64, p = 0.02). One subject had non-pathological head-impulse gain (0.82 ± 0.03) and high HITD-FT score (92%). One subject could read (93%) despite a low head-impulse gain (0.59 ± 0.03) performing re-fixation saccades. Summary Our study suggests that the recently proposed HITD-FT is an appropriate method to document the combined effect of VOR performance and re-fixation saccades in vestibular dysfunction. Testing dynamic vision with head movement characteristics closely related to subjects' daily activities makes the HITD-FT a suitable tool for assessing overall dynamic visual performance, e.g., to monitor progress during vestibular rehabilitation.